Vasopressors and Risk of Acute Mesenteric Ischemia: A Worldwide Pharmacovigilance Analysis and Comprehensive Literature Review - Jozwiak, Mathieu; Geri, Guillaume; Laghlam, Driss; Boussion, Kevin; Dolladille, Charles; Nguyen, Lee S. (Frontiers in Medicine, 2022)
Vasodilatory shock, such as septic shock, requires personalized management which include adequate fluid therapy and vasopressor treatments. While these potent drugs are numerous, they all aim to counterbalance the vasodilatory effects of a systemic inflammatory response syndrome. Their specific receptors include alpha- and beta-adrenergic receptors, arginine-vasopressin receptors, angiotensin II receptors and dopamine receptors. Consequently, these may be associated with severe adverse effects, including acute mesenteric ischemia (AMI). As the risk of AMI depends on drug class, we aimed to review the evidence of plausible associations by performing a worldwide pharmacovigilance analysis based on the World Health Organization database, VigiBase®. Among 24 million reports, 104 AMI events were reported, and disproportionality analyses yielded significant association with all vasopressors, to the exception of selepressin. Furthermore, in a comprehensive literature review, we detailed mechanistic phenomena which may enhance vasopressor selection, in the course of treating vasodilatory shock.